A Design of Experiment Approach to Optimize Spray-Dried Powders Containing Pseudomonas aeruginosaPodoviridae and Myoviridae Bacteriophages - Emilie Tabare; Tea Glonti; Christel Cochez; Cyrille Ngassam; Jean-Paul Pirnay; Karim Amighi; Jonathan Goole (Viruses, 2021)
In the present study, we evaluated the effect of spray-drying formulations and operating parameters of a laboratory-scale spray-dryer on the characteristics of spray-dried powders containing two Pseudomonas aeruginosa bacteriophages exhibiting different morphotypes: a podovirus (LUZ19) and a myovirus (14-1). We optimized the production process for bacteriophage-loaded powders, with an emphasis on long-term storage under ICH (international conference on harmonization) conditions. D-trehalose-/L-isoleucine-containing bacteriophage mixtures were spray-dried from aqueous solutions using a Büchi Mini Spray-dryer B-290 (Flawil, Switzerland). A response surface methodology was used for the optimization of the spray-drying process, with the following as-evaluated parameters: Inlet temperature, spray gas flow rate, and the D-trehalose/L-isoleucine ratio. The dried powders were characterized in terms of yield, residual moisture content, and bacteriophage lytic activity. L-isoleucine has demonstrated a positive impact on the activity of LUZ19, but a negative impact on 14-1. We observed a negligible impact of the inlet temperature and a positive correlation of the spray gas flow rate with bacteriophage activity. After optimization, we were able to obtain dry powder preparations of both bacteriophages, which were stable for a minimum of one year under different ICH storage conditions (up to and including 40 °C and 75% relative humidity).